The regulation of agricultural biotechnology - Evenson, Robert E. (Robert Eugene), 1934-; Santaniello, V. (CABI Pub., 2004)
The regulatory systems in place prior to the development and expansion of agricultural biotechnology are still responding to this new form of technology. Such systems include trade law, intellectual property law, contract law, environmental regulations and biosafety regulations. This book reviews these reforms which are aimed at achieving a regulatory system supported by consumers and other political groups. The 24 chapters have been developed from papers presented at a conference of the International Consortium on Agricultural Biotechnology Research, held in Italy in July 2002. Primary consideration is given to the relationship between these regulatory changes and innovation, market development and international trade. The chapters are presented in the 6 sections: introduction and overview (1 chapter); evolving regulation systems (6 chapters); regulation and innovation (5 chapters); regulations, market structures and innovation (4 chapters); regulation and market development (5 chapters); and economic impacts (3 chapters). A subject index is supplied. This book will be of interest to those working within biotechnology, law and agricultural economics.